Validation of Omni Scale of perceived exertion during prolonged cycling - Utter, A.; Kang, J.; Nieman, D. C.; Dumke, C.; McAnulty, S. R. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The present investigation was conducted to validate the OMNI ratings of perceived exertion (RPE) scale during prolonged cycle exercise when subjects were supplemented with either carbohydrate or placebo.